The Influence of Religious Activity Habituation on the Formation of Students’ Character at MI Al-Falah, Tigarun Village, Amuntai Tengah District, Hulu Sungai Utara Regency - Ria Susanti; Putri Roseana; Agus Diannor (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This research is motivated by the moral degradation occurring among children today, prompting schools to make efforts to address this issue. Schools have an important role in shaping the character of their students. Character building involves instilling habits that teach students which actions are good by engaging them in positive routine activities, enabling them to understand, internalize, and apply these values in daily life, such as religious activities conducted at school. The purpose of this study is to determine whether there is an influence of the habituation of religious activities on the character building of students at MI Al-Falah, Tigarun Village, Amuntai Tengah District, North Hulu Sungai Regency. This research is quantitative in nature. The sample consists of 33 students from grades 3 to 6. The sampling technique used is saturated sampling. Data collection techniques include questionnaires, documentation, and observation. Data analysis uses the Product Moment correlation formula. The results of this study indicate that the habituation of religious activities has an influence on the character building of students at MI Al-Falah, Tigarun Village, Amuntai Tengah District, North Hulu Sungai Regency, as evidenced by the correlation test showing that the Product Moment correlation coefficient (0.4751) is greater than the r-table values at the 5% (0.3440) and 1% (0.4421) significance levels. Thus, the results are significant, and it can be concluded that there is an effect of the habituation of religious activities on the character building of the students at MI Al-Falah, Tigarun Village, Amuntai Tengah District, North Hulu Sungai Regency